A dynamic simulation model for long-term hypertension progression - İncioğlu, Fırat. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Dynamics of blood pressure over the life span of human beings demonstrates a growth path. The most significant theories which aim to explain this trend adopt a kidneydependent approach. Structural reductions in the size of renal arterioles (vascular remodeling) and loss of nephrons are considered to be primarily responsible for the progressive increase in blood pressure. Dynamics of progression of blood pressure can most suitably be modeled by conceptualizing the problem as a long-term control of fluid excretion capacity. The goal of this thesis is to construct a dynamic simulation model that can realistically reproduce the long-term progression of blood pressure in healthy and in hypertensive subjects. For this purpose, a system dynamics model is built which focuses on systemic interactions that result in vascular remodeling in renal arterioles and loss of nephrons. These hypertensive mechanisms are integrated with a blood pressure control mechanism responsible for functional vasodilation of renal arterioles. For both normal and hypertensive subjects the model realistically reproduces the behavior of blood pressure, fluid volume, plasma renin and distribution of normal and remodeled nephrons. The reference behaviors of the model point out a number of important characteristics that differentiate blood pressure progression in essential-hypertensive and normal subjects. Experiments demonstrate that management of the number of remodeled arterioles over time should be an essential task in long-term blood pressure progression control. With proper control of remodeled arterioles, blood pressure of essential hypertensive subjects can be reduced back to normal and the longevity of adequate fluid excretion capacity can be greatly improved. Scenario runs with the simulation model help distinguish such successful policies from the ineffective interventions.
Keywords: Hypertension.